Sprawowanie sakramentu pokuty i pojednania "na odległość" - Janczewski, Zbigniew (Prawo Kanoniczne, 2007)
Individual and integral confession and absolution constitute the sole ordinary means by which a member of the faithful who is conscious of grave sin is reconciled with God and with the Church. Physical or moral impossibility alone excuses from such confession, in which case reconciliation may be attained by other means also (can. 960). The proper place for hearing sacramental confessions is a church or oratory. Except for a just reason, confessions are not to be heard elsewhere than in a confessional (can. 964). In the XVII century Holy See prohibited celebration of the sacrament of penance with the aid of letter. In the XIX century was the problem relative to confession by telephone. The opinion of Vatican Congregation s. Oficium to that question was not clear. Some authors think, that any priest can probably validly absolve by telephone in danger of death of penitent. In the beginning of the XXI century we ask about possibility confession by internet or mobile telephone 3G. This elaboration is a trial settlement the conditions of validly celebration of that sacrament by internet and mobile telephone in the future.